2016
DOI: 10.1002/2016gl068408
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal iron flux variability following rapid sea level changes

Abstract: Sea level changes associated with Pleistocene glacial cycles have been hypothesized to modulate melt production and hydrothermal activity at ocean ridges, yet little is known about fluctuations in hydrothermal circulation on time scales longer than a few millennia. We present a high‐resolution record of hydrothermal activity over the past 50 ka using elemental flux data from a new sediment core from the Mir zone of the TAG hydrothermal field at 26°N on the Mid‐Atlantic Ridge. Mir sediments reveal sixfold to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 42 publications
2
56
1
Order By: Relevance
“…They showed that the peaks in these fluxes lag the two previous maxima in the rate of sea-level decrease by about 15 kyr. Middleton et al [49] found that sediments from 26 • N on the Mid-Atlantic Ridge document an increase in elemental fluxes (Fe, Cu) in hydrothermal systems concomitant with the most rapid sea-level decrease leading to the last glacial maximum. Relatively short lags between peaks in rate of sea-level change and peaks in melt flux are consistent with our models forced with the sea-level reconstruction of the Middle and Upper Pleistocene.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the peaks in these fluxes lag the two previous maxima in the rate of sea-level decrease by about 15 kyr. Middleton et al [49] found that sediments from 26 • N on the Mid-Atlantic Ridge document an increase in elemental fluxes (Fe, Cu) in hydrothermal systems concomitant with the most rapid sea-level decrease leading to the last glacial maximum. Relatively short lags between peaks in rate of sea-level change and peaks in melt flux are consistent with our models forced with the sea-level reconstruction of the Middle and Upper Pleistocene.…”
Section: Discussionmentioning
confidence: 99%
“…The seafloor bathymetry, primarily determined by oceanic crustal thickness, suggests a sensitivity of mid-ocean ridge volcanism to sea level changes on Milankovitch timescales (e.g., Crowley et al, 2015;Lund & Asimow, 2011;Schindlbeck et al, 2018;Tolstoy, 2015). A peak of hydrothermal activity~15 ka after the last glacial maximum on the Mid-Atlantic Ridge (Middletone et al, 2016), Juan de Fuca Ridge (Costa et al, 2017), and at the East Pacific Rise (Lund et al, 2016) has been interpreted as the delayed melt formation following the hydrostatic pressure minimum.…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%
“…Along with higher dust flux, 15 N∕ 14 N ratios from planktonic foraminifera in SO sediment cores have been interpreted as higher productivity and more efficient nutrient utilization in the LGM compared to the PI (Martínez-García et al, 2014). Meanwhile, Middleton et al (2016) and Lund et al (2016) proposed that hydrothermal flux may have been higher during the LGM due to lower water column pressure on hydrothermal vents. Numerous modeling efforts have studied effects of iron fertilization on the LGM carbon cycle.…”
Section: 1002/2016pa003077mentioning
confidence: 99%